Corporate Tax Rate and Capital Structure Decision of Nigeria Deposit Money Bank - Abiodun Rafiat, Ayeni-Agbaje; Folakemi Serifat, Orimogunje (EuroEconomica, 2025)
This study examined the effect of corporate tax rate on capital structure decision in Nigeria deposit money bank, it specifically examined the effect of effective tax rate (ETR) and statutory corporate tax rate (SCTR) on the leverage of Deposit Money Banks (DMBs) in Nigeria. An ex-post facto research design was adopted, and data were sourced from the audited annual financial statements of listed DMBs obtained from the Nigerian Exchange Group. Using purposive sampling, 12 DMBs were selected from the population of banks operating in Nigeria between 2015 and 2024. Data reliability was ensured through cross-validation with regulatory filings, while analytical rigor was maintained using panel regression techniques with E-Views 12. The results revealed that ETR (β = 0.417, p < 0.01) had a strong and statistically significant effect on leverage, while SCTR (β = 0.093, p > 0.05) exerted only a weak and insignificant influence. Additional findings showed that profitability negatively affected leverage (β = –0.281, p < 0.05), size positively influenced leverage (β = 0.326, p < 0.05), and liquidity negatively impacted leverage (β = –0.214, p < 0.05). The model explained 69.5% of the variation in leverage (R² = 0.695), affirming the relevance of trade-off theory which emphasized the balancing of tax benefits and financial distress costs in financing decisions. The study concluded that capital structure choices of DMBs in Nigeria were more sensitive to effective tax burdens than to statutory tax rates, particularly under the 2025/2026 corporate tax reforms which introduced a 15% minimum ETR and additional levies. It recommended that banks strengthen tax planning strategies and align financing structures with evolving tax obligations to enhance competitiveness and regulatory compliance.